TEOLOGI DAN FILSAFAT DARI POLEMIK DISKURSIF TEOSENTRIS MENUJU APLIKATIF ANTROPOSENTRIS - Titis Rosowulan (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2019)
Theology and philosophy, as a science, have a long history of birth in the Islamic world. However, it does not mean that the studies that have been carried out several centuries ago must be applied in the same way in contemporary times. In Islamic scientific history, philosophy and theology have a thick theological style, in stead of the discursive method of study. In the context of history, such patterns and methods are still understandable, because the social conditions of the people at that time did demand that. The problem is that such methods and patterns are often used by reviewers to discuss this two sciences at this time. Finally, this kind of study raises a polemic and creates an atmosphere of hostility in contemporary society. Therefore, a new approach is needed in reviewing both. The theological discursive approach must be replaced with an anthropocentric applicative approach, so that the development of these two sciences can have more beneficial value for society. This research attempts to direct the development of the two sciences by using the theory of shifting paradigm popularized by Thomas Kuhn.